Genetic variant in the 3′-untranslated region of the COX2 gene is associated with type 2 diabetes: A hospital-based case-control study - Ozbayer, Cansu; Kebapci, Medine Nur; Degirmenci, Irfan; Yagci, Emine; Gunes, Hasan Veysi; Kurt, Hulyam (Prostaglandins, leukotrienes and essential fatty acids, 2018)
•We aimed to investigate the relationship between variants of COX-2 gene which is one of the key components of the inflammatory pathway, and T2DM risks.•A significant association was observed for genotype distribution of COX2 rs5275 site between control and T2DM cases (p = 0.042).•In a dominant model, the cases who had at least one copy of allele C, were at increased risk of T2DM (p = 0.016).•We found no significant association for the COX2 rs689466 domain by evaluating homozygous, heterozygous, dominant, and recessive models (p > 0.05). Type 2 diabetes (T2DM) is caused by the decreased β-cell mass and insulin deficiency, and disease is characterized by hypoglycemia. The insulin resistance also plays an important role in T2DM pathogenesis. Insulin resistance is the reduced biological response to insulin at the normal concentration in the circulation and develops with the influence of environmental factors with genetic abnormalities. In recent years, it has been reported that inflammatory pathway causes activation of the insulin resistance. Chronic inflammation inhibits the insulin sensitivity through activation of signaling pathways which are directly associated with the key components of insulin signaling pathway. Cyclooxygenase (COX) enzymes are key enzymes that catalysis prostaglandin synthesis from arachidonic acid. COX2 is an inducible COX isoform and that plays an important role in inflammatory process by leading the synthesis of pro- and anti- inflammatory prostaglandins. In our study, we aimed to investigate the relationship between variants of COX-2 gene which is one of the key components of the inflammatory pathway, and T2DM risks. In this study, we evaluated rs5275 and rs689466 variants located on the COX-2 gene by PCR–RFLP in 100 T2DM patients and 100 control subjects. The interaction among COX2 variants and T2DM was analyzed using appropriate methods. The both variants were in Hardy–Weinberg equilibrium in patients and controls (p > 0.05). A significant association was observed for genotype distribution of COX2 rs5275 site between control and T2DM cases (p = 0.042). In a dominant model, the cases who had at least one copy of allele C, were at increased risk of T2DM (p = 0.016). We found no significant association for the COX2 rs689466 domain by evaluating homozygous, heterozygous, dominant, and recessive models (p > 0.05). According to our data, the rs5275 variant of the COX2 in the 3′-UTR may contribute to the etiology or modulate the risk of T2DM, whereas the rs689466 variant of the COX2 gene is not associated with T2DM risk.